RE-DESAIN INTERIOR SELF-SERVICE SHOWROOM PLASTIC RECYCLE DI DENPASAR-BALI (Jurnal iSpectrum, 2025)
Plastic waste is a global problem that is increasing along with the growth of plastic consumption in society. Billions of tons of plastic waste are always produced causing serious impacts on the environment such as water and soil pollution and threats to biological ecosystems. This is caused by a lack of public awareness of the dangers and proper methods of processing abundant plastic. By designing the Self Service & Showroom Plastic Recycle, it is hoped that it can tackle plastic waste and provide education and experience in processing plastic waste to the public.